POTENSI PEMANFAATAN LIMBAH AIR CUCIAN BERAS PADA TANAMAN PAKCOY (BRASSICA RAPA L.) - Maria Paulina; Santa Maria Lumbantoruan; Aella Septiani (LPPM Universitas Bina Insan, 2020)
Pakcoy as a type of vegetable that we often encounter on the market. This plant can be cultivated easily, and can be consumed directly or processed into complementary vegetables in meatballs, chicken noodles, and other types of food. Excessive use of chemical fertilizers will cause soil damage in the long term. Reducing chemical fertilizers can be done by giving rice washing water, because usually when washing rice, the water used is just thrown away. In fact, this rice washing water waste has the potential as liquid organic fertilizer. The purpose of this study was to determine the effect of rinsing rice washing water on the growth and yield of pakcoy plants. The research design used a randomized block design (RAK) with a single factor, namely the rice washing water rinse, namely C0 = control, C1 = the first rinse of rice washing water, C2 = the second rinse of rice washing water, and C3 = the third rinse of rice washing water. The parameters observed were plant height, number of leaves, plant diameter, fresh root weight, and total fresh weight. The results showed that rice washing water rinse had no significant effect on all observed parameters. However, C3 treatment has the greatest value for all observations compared to the control treatment, C1, or C2.